2018
DOI: 10.1101/479618
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Colistin kills bacteria by targeting lipopolysaccharide in the cytoplasmic membrane

Abstract: Tel: 0044 (0)207 594 2072 23 Fax: 0044 (0)207 594 3096 24 a.edwards@imperial.ac.uk 25 26 Keywords: Colistin / polymyxin / Pseudomonas / E. coli / Klebsiella / lipopolysaccharide / resistance / MCR-1 27 28 Running title: Colistin mechanism of action 29 30 31 32 33 2 Summary 34 Colistin is an antibiotic of last resort for infections caused by drug-resistant Gram-negative pathogens such 35as Pseudomonas aeruginosa and Escherichia coli. For this reason, high rates of treatment failure and 36 increasing resistance … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 74 publications
(90 reference statements)
1
31
0
2
Order By: Relevance
“…Glass vials were used for these experiments because colistin can bind plastic and we wished to minimise loss to binding of the culture vessel in order to measure the proportion of colistin entering the biofilms as accurately as possible. Addition of the BODIPY-tag has been shown to reduce bactericidal activity in planktonic culture (19), and a pilot experiment using PA14, SED6 and SED8 had confirmed that the tag significantly reduced activity in our biofilm assay ( Figure S3). , therefore fluorescence values from samples exposed to BODIPY-colistin were standardised by subtracting the mean fluorescence measured in homogenate/surrounding ASM from tissues infected by the same strain but exposed to SCFM with no BODIPYcolistin.…”
Section: Table S1mentioning
confidence: 52%
See 3 more Smart Citations
“…Glass vials were used for these experiments because colistin can bind plastic and we wished to minimise loss to binding of the culture vessel in order to measure the proportion of colistin entering the biofilms as accurately as possible. Addition of the BODIPY-tag has been shown to reduce bactericidal activity in planktonic culture (19), and a pilot experiment using PA14, SED6 and SED8 had confirmed that the tag significantly reduced activity in our biofilm assay ( Figure S3). , therefore fluorescence values from samples exposed to BODIPY-colistin were standardised by subtracting the mean fluorescence measured in homogenate/surrounding ASM from tissues infected by the same strain but exposed to SCFM with no BODIPYcolistin.…”
Section: Table S1mentioning
confidence: 52%
“…First, colistin is widely prescribed for P. aeruginosa infection in CF and is commonly administered by inhalation; this means that topical lab exposure of biofilms to colistin, by spiking the surrounding culture medium, likely mimics in vivo exposure better than in the case of antibiotics that are only administered orally or through IV. Second, fluorescently-labelled colistin was available from colleagues, opening up the possibility to assay colistin concentration in biofilm via fluorimetry (19). Finally, colistin is able to bind the P. aeruginosa exopolymer Psl (20) and extracellular lipopolysaccharide (21), and may adsorb to outer membrane vesicles (22) -all of which may be present in P.…”
Section: Full Textmentioning
confidence: 99%
See 2 more Smart Citations
“…Colistin specifically targets Gram-negative bacteria by binding to the anionic phosphate groups of the lipid A moiety of lipopolysaccharides (LPS) through electrostatic interactions (79). Colistin destabilizes the outer membrane, but the subsequent disruption of the inner membrane ultimately leads to cell death (9, 10). Acquired colistin resistance has been reported in various Gram-negative bacteria that were isolated from clinical, veterinary, and environmental sources (1113).…”
Section: Introductionmentioning
confidence: 99%